Amplified OTDR Fiber Tree Network in Water Surface Detection - Yamabayashi, Yoshiaki (Current Approaches in Engineering Research and Technology Vol. 8, 2024)
For disaster prevention and control, water levels at remote places, such as dams, and lakes, need to be always monitored. Similar cases can be found in liquid tanks in factories or reservoirs in waterworks. Conventional sensors that need to be powered electrically are susceptible to power outages and possible risk of discharge sparks. A sensor design is required to make the network all optical and remove the need for an electric power supply for the distributed sensors. To monitor water levels at long distances, a fiber-based time-domain reflectometry network with optical amplification is proposed. A collimator at each fiber end of a tree-type network retrieves 1.55 \(μ\)m wavelength pulses that are reflected from remote liquid surfaces. In the present paper a successful simultaneous monitoring experiment of two water levels in the laboratory, as well as a trial for detecting a disturbed surface by beam-expanding and its theoretical background are reported.